Differences in mortality in Switzerland by citizenship during the first and second COVID-19 waves: Analysis of death statistics - Plümecke, Tino; Mikosch, Heiner; Mohrenberg, Steffen; Supik, Linda; Bartram, Isabelle; Ellebrecht, Nils; zur Nieden, Andrea; Schnieder, Laura; Schönberger, Hannah; Schulze-Marmeling, Charlotte; Gutzeit, Andreas (Frontiers in Public Health, 2022)
Background Early in the COVID-19 pandemic, it became apparent that members of marginalized populations and immigrants were also at risk of being hospitalized and dying more frequently from COVID-19. To examine how the pandemic affected underserved and marginalized populations, we analyzed data on changes in the number of deaths among people with and without Swiss citizenship during the first and second SARS-CoV-2 waves. Method We analyzed the annual number of deaths from the Swiss Federal Statistical Office from 2015 to 2020, and weekly data from January 2020 to May 2021 on deaths of permanent residents with and without Swiss citizenship, and we differentiated the data through subdivision into age groups. Results People without Swiss citizenship show a higher increase in the number of deaths in 2020 than those who were Swiss citizens. The increase in deaths compared to the previous year was almost twice as high for people without Swiss citizenship (21.8%) as for those with it (11.4%). The breakdown by age group indicates that among people between the ages of 64 and 75, those without Swiss citizenship exhibited an increase in mortality (21.6%) that was four times higher than that for people with Swiss citizenship (4.7%). Conclusion This study confirms that a highly specialized health care system, as is found in Switzerland, does not sufficiently guarantee that all parts of the population will be equally protected in a health crisis such as COVID-19.